A method for studying model hamiltonians : a minimax principle for problems in statistical physics - Bogoliubov, N. N. (Nikolai Nikolaevich), 1909-1992 (International series of monographs in natural philosophy ;, 1972)
A Method for Studying Model Hamiltonians: A Minimax Principle for Problems in Statistical Physics centers on methods for solving certain problems in statistical physics which contain four-fermion interaction. Organized into four chapters, this book begins with a presentation of the proof of the asymptotic relations for the many-time correlation functions. Chapter 2 details the construction of a proof of the generalized asymptotic relations for the many-time correlation averages. Chapter 3 explains the correlation functions for systems with four-fermion negative interaction. The last chapter sh.